Generating and Facilitating Effective Online Learning through Discussion - Maddix, Mark A. (Christian education journal, 2012)
In Christian higher education, most teaching and learning has been confined to the traditional classroom. However, with the advent of computer technology many universities and seminaries are offering online courses and programs. These online courses provide facilitators and teachers with a different learning context. One of the most important social learning components of online learning is discussion forums. These forums provide a context for faculty-student and student-student interaction. For teachers facilitating discussion, this can become an overwhelming task, especially when there is too much or not enough student interaction. This article addresses such questions as: How can teachers ensure that discussion is contributing to learning. How much interaction is necessary and what constitutes effective interaction? How can we ensure that students engage in thoughtful discussion?This article explores how teachers can facilitate effective online learning through discussion. The article also presents a framework for effective online discussion called the Community Inquiry Model (Garrison & Anderson, 2011). The article provides guidelines for teachers to develop discussion board rubrics and effective faculty-student and student-student interaction in online courses. The article concludes by providing best practices of online discussion based on current research and personal experience in teaching online courses.